Preparation method of on-off-on fluorescent nano sensor based on NCl-CQDs

The complex process of existing CQDs synthesis is solved by constructing an "on-off-on" fluorescent nanosensor using nitrogen-chloro-codoped carbon quantum dots (NCl-CQDs) with 2,6-dichloroindiphenol sodium and ascorbic acid (AA). and the problem of low fluorescence quantum yield, high sensitivity detection of ascorbic acid is achieved and has good application prospects.

CN119394977AActive Publication Date: 2025-02-07QINGHAI UNIV FOR NATITIES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411305071.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-02-07
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

Existing carbon quantum dots (CQDs) have complex synthesis processes, time-consuming and low fluorescence quantum yields, which limits their wide application in the fields of biosensing and other fields.

Method used

Using nitrogen-chloro-codoped carbon quantum dots (NCl-CQDs) as fluorescent probes, combined with 2,6-dichloroindiphenol sodium (DCIP) as fluorescent quencher and ascorbic acid (AA) as fluorescent recovery agents, through specific The sample loading sequence is used to construct a "on-off-on" fluorescent nanosensor.

Benefits of technology

It realizes high sensitivity detection of ascorbic acid, has good selectivity and linear relationship, can accurately detect the content of AA in actual samples, and has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119394977A_ABST
    Figure CN119394977A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fluorescent nano sensors, and particularly relates to a preparation method of an on-off-on fluorescent nano sensor based on NCl-CQDs (nitrogen-chlorine co-doped carbon quantum dots), nitrogen-chlorine co-doped carbon quantum dots NCl-CQDs are used as a fluorescent needle, 2, 6-dichloroindophenol sodium DCIP is used as a fluorescence quenching agent, ascorbic acid AA is used as a fluorescence restorer, and the fluorescent nano sensor is prepared by a one-step method. The three are specifically combined under a specific sample adding sequence to obtain the'on-off-on 'fluorescent nano sensor; the preparation method specifically comprises the following steps: taking glucose Glu, ethylenediamine EDA and concentrated hydrochloric acid HCl as raw materials, and preparing nitrogen-chlorine co-doped carbon quantum dots NCl-CQDs by adopting a dehydration heat release carbonization method; when the excitation wavelength is 390 nm, the maximum fluorescence emission wavelength of the NCl-CQDs is 467 nm, and at the moment, the fluorescence intensity is in an ON state; when DCIP is introduced into an NCl-CQDs solution, due to the photoinduced electron transfer effect, fluorescence of NCl-CQDs is quenched, the fluorescence signal intensity is closed, and the NCl-CQDs are in an OFF state; aA is continuously introduced into an NCl-CQDs / DCIP system, so that the fluorescence intensity of NCl-CQDs can be remarkably recovered, and at the moment, the fluorescence intensity is in an ON state.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fluorescent nanosensors, and specifically is a method for preparing an "on-off-on" fluorescent nanosensor based on NCl-CQDs. Background Art

[0002] Carbon Quantum Dots (CQDs) are new fluorescent carbon nanomaterials composed of dispersed spherical particles with extremely small size (≤10nm or less). They have the advantages of low cost, high stability, good biocompatibility, and no need for complex steps. As a new, low-toxic nanomaterial with excellent optical properties, CQDs have different application prospects in various fields, such as biosensing, bioimaging, photodynamic therapy, drug delivery, etc. Due to its unique properties and wide application, CQDs are synthesized in large quantities. However, all methods have the disadvantages of complex synthesis process, time-consuming, and complex reaction conditions, which limit their wide application. In addition, most CQDs have defects such as relatively low fluorescence quantum yields (QY), few active sites, and poor selectivity, which are usually not well used in practical applications. Therefore, in order to improve the optical and chemical properties of carbon dots, previous researchers proposed a method of heteroatom doping. Among different heteroatoms, nitrogen-doped CQDs show higher QY, which is beneficial to stabilize the surface defects of CQDs, thereby improving fluorescence emission. ] However, pure nitrogen doping may not meet specific performance requirements in some aspects, such as some special catalytic reactions or optical applications. Among the many carbon dot modification methods reported, co-doping of nitrogen atoms with other heteroatoms is the most studied method, mainly including N / S, N / B, N / F, N / P, N / Mg, N / Cu and other co-doping methods.

[0003] Therefore, based on these studies, there are more and more people working on choosing N and Cl as co-dopants, which have several significant advantages over single-doped N or Cl carbon dots, including enhanced fluorescence emission, higher sensitivity, and the ability to tune the optical and electrical properties of quantum dots. In 2021, Yin synthesized new NCl co-doped carbon dots (NCl-CQDs) using choline chloride / urea DES and glycine as C atom sources. The prepared NCl-CQDs have strong fluorescence emission and good thermal stability. The NCl-CQDs fluorescent probe was used to perform high-sensitivity analysis of trace amounts of poppy shells in food by determining morphine, the main alkaloid of poppy shells. In 2022, Cao et al. prepared nitrogen-chlorine co-doped CQDs (R-CQDs) with bright red fluorescence using 4-chlorobenzene-1,2-diamine, dilute hydrochloric acid and deionized water by a simple one-step hydrothermal method, with red fluorescence of high PLQY. In 2023, R Tabaraki et al. prepared NCl-doped carbon dots (NCl-CQDs) in choline chloride-glycerol deep eutectic solvent (DES) by microwave method, and the surface was modified with vancomycin for the detection of Staphylococcus aureus (S. aureus) bacteria. Therefore, based on the previous research, this study is committed to exploring the synthesis of NCl-CQDs to achieve the detection of AA.

[0004] Sodium 2,6-dichloroindophenol (DCIP) is a dark blue crystalline powder that is soluble in ethanol and ether, slightly soluble in water, but insoluble in non-polar solvents. As a well-known analytical reagent, DCIP has redox properties and can be used for volumetric and photometric determination of ascorbic acid (AA) and other reducing agents. Because of its obvious color change, it is also commonly used in kits such as enzyme activity assays, enzyme-linked immunosorbent assays, and drug assays. When the pH value is higher than 6.0, the oxidized form of DCIP aqueous solution is dark blue in the solution with an absorption spectrum of approximately 420-750nm, while the reduced form of DCIP is colorless. Due to the photoinduced electron transfer effect (PET) between NCl-CQDs and DCIP in the system, fluorescence quenching occurs.

[0005] It is well known that there is a specific reduction reaction between 2,6-dichloroindophenol sodium and ascorbic acid. [, they are often used as active molecular pairs in signal switch sensing systems. Ascorbic acid (AA, also known as vitamin C) is a highly water-soluble polyhydroxy compound and an important nutrient. It plays a leading role in human health in various biological processes by reducing oxidative damage to proteins, DNA and lipids. Secondly, it has a strong reducing property and can participate in redox reactions and various hydroxylation reactions in the body. When the body lacks ascorbic acid, it may produce symptoms such as limb weakness and lack of energy. In severe cases, it may also cause bone pain, osteoporosis and other diseases. In general, ascorbic acid can also promote the synthesis of collagen and connective tissue in the body, help the recovery and healing of wounds, and can also remove free radicals in the body, prevent cells from suffering oxidative damage, and improve the body's immune capacity. It is estimated that the tolerable daily intake of AA is 2000mg / d. As an indispensable micronutrient, AA cannot be synthesized in the body and must be ingested from exogenous sources such as fruits or dining tables to meet the body's needs. Therefore, it is necessary to conduct a large number of tests on AA in the body. At present, the main methods for detecting AA include electrochemical analysis, chemiluminescence, fluorescence spectroscopy and liquid chromatography. Among them, fluorescence spectroscopy has attracted much attention due to its advantages such as simple operation, sensitivity and visualization of detection results. Summary of the invention

[0006] The purpose of the present invention is to address the problems existing in the prior art and provide a method for preparing an "on-off-on" fluorescent nanosensor based on NCl-CQDs.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A preparation method of an "on-off-on" fluorescent nanosensor based on NCl-CQDs, characterized in that: nitrogen-chlorine co-doped carbon quantum dots NCl-CQDs are used as fluorescent needles, 2,6-dichloroindophenol sodium DCIP is used as a fluorescence quencher, and ascorbic acid AA is used as a fluorescence recovery agent. The three are specifically combined in a specific sample addition order to obtain an "on-off-on" fluorescent nanosensor; the specific steps are as follows:

[0009] Step 1: Using glucose Glu, ethylenediamine EDA and concentrated hydrochloric acid HCl as raw materials, NCl-CQDs with a nitrogen-chlorine co-doped carbon quantum dot concentration of 44.4 μM were prepared by dehydration exothermic carbonization method; when the excitation wavelength was 390 nm, the maximum fluorescence emission wavelength of NCl-CQDs was 467 nm, and the fluorescence intensity was in the "ON" state;

[0010] Step 2: When 1 mL of 30.77 μM DCIP was introduced into 1 mL of 44.4 μM NCl-CQDs solution, at an excitation wavelength of 390 nm, the fluorescence of NCl-CQDs was quenched due to the photoinduced electron transfer effect, and the fluorescence emission intensity dropped from 910 nm to about 50 nm. At this time, the fluorescence was in the "OFF" state.

[0011] Step 3. Continuously introducing 85.5 μM AA into the NCl-CQDs / DCIP system can significantly restore the fluorescence intensity of NCl-CQDs. When the excitation wavelength is 390 nm, the signal intensity can increase from 148 nm to about 748 nm, at which time the fluorescence intensity is in an "ON" state; thus, an "on-off-on" fluorescence nanosensor of NCl-CQDs / 2,6-dichloroindophenol sodium + AA is obtained.

[0012] Preferably, the preparation steps of the nitrogen-chlorine co-doped carbon quantum dots NCl-CQDs are as follows:

[0013] Step (1) 0.8 g glucose and 12 ml EDA were completely dissolved in 20 mL ultrapure water by ultrasound and vortexing;

[0014] Step (2) Add 4 ml of concentrated hydrochloric acid to the above mixed solution, releasing a large amount of white smoke and heat. After cooling to room temperature, a brown-yellow substance is obtained;

[0015] Step (3) The brown-yellow substance was dissolved in 50 ml of ultrapure water, and the solution was then centrifuged at 4000 rpm for 10 min, and then microfiltered using a 0.22 μM filter to obtain a brown solution, and the solution was freeze-dried to obtain pure NCl-CQDs brown solid powder.

[0016] Preferably, in step 1, the fluorescence quantum yield of the prepared NCl-CQDs is 48.5%

[0017] Preferably, in step 2, the reaction time is 5 min.

[0018] Preferably, in step three, the reaction time is 1.5 min.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The present invention utilizes a dehydration carbonization method to synthesize NCl-CQDs. The synthesized NCl-CQDs particles are evenly distributed and have good dispersibility. The average particle size is 2.96 nm and has obvious luminescence characteristics and excitation wavelength dependence.

[0021] 2. The present invention establishes a relatively novel "switch-on" method for detecting AA based on the NCl-CQDs fluorescent probe. In the experiment, NCl-CQDs were used as fluorescent probes, and based on the principle that the fluorescence spectrum of NCl-CQDs changes due to the photoinduced electron transfer between 2,6-dichloroindophenol sodium and NCl-CQDs, an "on-off" type fluorescence sensor of NCl-CQDs and 2,6-dichloroindophenol sodium was constructed. Then, by using the specific reaction between 2,6-dichloroindophenol sodium and AA, AA was continuously introduced into the system to construct an "off-on" type fluorescence sensor. Based on the specific reaction between AA and 2,6-dichloroindophenol sodium, AA competes with 2,6-dichloroindophenol sodium on the surface of NCl-CQDs, thereby restoring the UV-visible absorption spectrum and fluorescence signal of NCl-CQDs, and then an "on-off-on" type fluorescence sensor of NCl-CQDs / 2,6-dichloroindophenol sodium + AA was established.

[0022] 3. The fluorescence analysis method established in the present invention can be used for the detection of AA in actual sample serum through spike recovery, indicating that the fluorescence sensing system has better utilization value for AA in actual complex samples. Compared with traditional detection methods, this method has good application prospects for monitoring the health level of the human body. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the use of NCl-CQDs for DCIP and AA detection in the present invention;

[0024] Figure 2 In the figure, A and B are TEM images of NCl-CQDs at 10nm and 20nm scales, respectively; C is the lattice spacing of the HRTEM image of NCl-CQDs; D is the particle size distribution histogram of NCl-CQDs; E is the XRD spectrum of NCl-CQDs; F is the Raman scattering image of NCl-CQDs;

[0025] Figure 3 In the figure, A is the UV-visible absorption, excitation spectrum and emission spectrum of NCl-CQDs (inset: images of NCl-CQDs under visible light and 365nm UV light); B is the fluorescence emission spectrum of NCl-CQDs at different excitation wavelengths (350-450nm); C is the total luminescence spectrum of NCl-CQDs (220-800nm); D is the CIE color coordinates of NCl-CQDs;

[0026] Figure 4 In the figure, A is the XPS spectrum of NCl-CQDs; (B) high-resolution XPS spectra of C-1s, (C) O-1s, (D) N-1s and (E) Cl-2p; (F) FT-IR spectrum of NCl-CQDs.

[0027] Figure 5 In the figure, the fluorescence intensity of NCl-CQDs corresponding to different xenon lamp irradiation time (A), different storage time (B), and different NaCl solution concentration (C);

[0028] Figure 6 For the construction of "ON-OFF-ON" fluorescence sensing system;

[0029] Figure 7 In the figure, A is the optimization of the reaction time between NCl-CQDs and DCIP; B is the optimization of the reaction time between NCl-CQDs-DCIP system and AA.

[0030] Figure 8 is the fluorescence spectrum of NCl-CQDs under 0-30.77 μM DCIP conditions;

[0031] Fig. 9 The effect of different substances on the fluorescence emission intensity of NCl-CQDs / DCIP system;

[0032] Fig.10 In the figure, A is the effect of different concentrations of AA (9.09-85.5 μM) on the fluorescence spectrum of the NCl-CQDs / DCIP system; B is the curve relationship obtained by the effect of different concentrations of AA on the fluorescence intensity of the NCl-CQDs / DCIP system; C and D are the piecewise linear relationships between the fluorescence intensity of the NCl-CQDs / DCIP system and different concentrations of AA.

[0033] Fig.11 In the figure, A is the "ON-OFF-ON" fluorescence sensing system; B and C are the UV-visible absorption spectra of various substances. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0035] Example 1 Experiment

[0036] 1. Materials and instruments

[0037] All reagents were of analytical reagent grade and used without further purification. Glucose (Glu) was purchased from Shanghai Wokai Biotechnology Co., Ltd., ascorbic acid was purchased from Shanghai McLean Biochemical Technology Co., Ltd., 11 amino acids (L-alanine, L-cysteine, L-threonine, L-arginine, L-histidine, L-methionine, L-leucine, L-serine, L-aspartic acid, L-valine, L-isoleucine) were purchased from Shanghai Aladdin Pharmaceutical Co., Ltd., 2,6-dichloroindophenol sodium was purchased from Shanghai Zhongqin Chemical Reagent Co., Ltd. (Shanghai, China). Ethylenediamine was purchased from Tianjin Damao Chemical Reagent Factory, and hydrochloric acid was purchased from Tianjin Hedong District Hongyan Reagent Factory (Tianjin, China). Metal ion solution preparation reagents were purchased from Sinopharm Chemical Reagent Co., Ltd. (Shenyang, China).

[0038] The samples were weighed using an electronic balance of model FA2104 (Shanghai Yuheng Scientific Instrument Co., Ltd., China). Transmission electron microscopy images were obtained using a JEM-2100F microscope (JEOL, Japan). X-ray powder diffraction patterns of the samples were collected using a Bruker D2 phase-shift diffractometer. Fluorescence spectra were measured using an RF-5301-PC fluorescence spectrometer (Shimadzu Corporation, Tokyo, Japan). UV-visible absorption spectra were recorded on a T6 New Century UV-Vis spectrophotometer produced by Beijing General Instrument Co., Ltd. (Beijing Puxi General Instrument Co., Ltd., China). X-ray photoelectron spectroscopy (XPS) was performed on an ESCALAB250Xi instrument. Fourier transform infrared spectroscopy (FT-IR) was measured by an IRPrestige21 spectrometer from Shimadzu Corporation, Tokyo, Japan. The CNC ultrasonic cleaning machine used a KH-300DE model (Kunshan Hechuang Ultrasonic Instrument Co., Ltd., China).

[0039] 2. Synthesis of NCl-CQDs

[0040] NCl-CQDs were synthesized by dehydration exothermic carbonization method using glucose (Glu), ethylenediamine (EDA) and concentrated hydrochloric acid as raw materials. First, 0.8g glucose and 12ml EDA were completely dissolved in 20mL ultrapure water by ultrasound and vortexing. 4ml concentrated hydrochloric acid was added to the above mixture, releasing a large amount of white smoke and heat. After cooling to room temperature, a brown-yellow substance was obtained, which was dissolved in 50ml ultrapure water. The solution was then centrifuged at 4000rpm for 10min, and then microfiltered using a 0.22μM filter to obtain a brown solution. The solution was freeze-dried to obtain pure NCl-CQDs brown solid powder. Finally, the black-brown solid powder was stored in a refrigerator at 4°C for further characterization and application.

[0041] 3. Calculation of fluorescence quantum yield

[0042] Fluorescence quantum yield (QY) is an important luminescence parameter of fluorescent substances, which is defined as the ratio of the number of fluorescent photons emitted by the fluorescent substance after absorbing light to the number of photons of the excitation light absorbed. The larger the value of QY, the stronger the fluorescence of the fluorescent substance, but its value is generally less than 1 according to the definition. The calculation of QY generally adopts the reference method, by comparing the integrated emission spectrum and absorbance of the fluorescent substance to be tested and the substance with known fluorescence quantum yield under the same measurement conditions. Quinine sulfate (QY = 54%) with a known fluorescence quantum yield is used as a standard substance to calculate the fluorescence quantum yield of NCl-CQDs. 0.04g of quinine sulfate is diluted to a constant volume with 0.05mol / l sulfuric acid solution, and 0.05mol / l sulfuric acid solution is used as a reference. The maximum absorption wavelength of the test fluorescence is used as the excitation wavelength. The fluorescence emission intensity at the excitation wavelength is measured by a fluorescence spectrophotometer, and the absorbance of the quinine sulfate solution at the wavelength is measured by a UV-visible spectrophotometer.

[0043]

[0044] Where I is the fluorescence integrated area of ​​the emission spectrum, A is the UV-visible absorbance at the fluorescence excitation wavelength, and η is the refractive index of the solvent (the refractive index of solvent water is 1.33, and the refractive index of concentrated sulfuric acid solution is 1.418).

[0045] 4. Construction of the sensing system

[0046] NCl-CQDs and DCIP were used as fluorescent probes to detect AA. In order to construct the NCl-CQDs / DCIP fluorescence sensing platform, 30 μl of NCl-CQDs were mixed with DCIP of different concentrations, and the fluorescence emission intensity was measured at an excitation wavelength of 390 nm. The concentration ratio with the best quenching effect was taken as the optimal system. Subsequently, different concentrations of AA were added to the NCl-CQDs / DCIP sensing system, and the resulting fluorescence spectra were recorded at an excitation wavelength of 390 nm. The concentration ratio with the best recovery effect was taken as the optimal system.

[0047] 5. Detection of DCIP and AA in actual samples

[0048] The human blood samples used for actual sample analysis were from the Fourth People's Hospital of Qinghai Province. The fresh blood samples were left to stand at room temperature for 30 minutes, centrifuged at 10,000 r / min for 25 minutes, and then the supernatant was filtered with a 0.22nm microporous filter to remove large particle impurities. Then 1ml of the supernatant was diluted 200 times to obtain serum samples. Serum samples from different time periods were added with different concentrations of AA to detect their fluorescence intensity. The reliability and accuracy of the fluorescence sensing system for AA detection were demonstrated by the spike recovery rate.

[0049] Example 2

[0050] 1. TEM and XRD characteristics of NCl-CQDs

[0051] To prove the successful synthesis of NCl-CQDs, transmission electron microscopy and XRD were used to characterize the NCl-CQDs. Figure 2 As shown in Figure 2, the morphology, particle size and dispersion of the synthesized NCl-CQDs were characterized by transmission electron microscopy. Figure 2 A) and 20nm( Figure 2 B) shows that the prepared NCl-CQDs are composed of dispersed spherical carbon particles with extremely small size, spherical morphology, uniform particle size and good dispersion. Figure 2 C) It can be clearly observed that the prepared NCl-CQDs have obvious crystalline features, and the lattice spacing is measured to be 0.23nm. Figure 2 As shown in D, the particle size distribution of the synthesized NCl-CQD was studied, and the results showed that its particle size range was 1.5-5.5nm, and the average particle size was 2.96nm. In addition, the X-ray diffraction pattern ( Figure 2 E) A strong diffraction peak appears at 2θ = 22.71°, corresponding to the (002) crystal plane of the graphite structure, indicating the presence of highly disordered carbon atoms. According to the above results, the synthesized NCl-CQDs have a highly crystalline and graphitized structure. Figure 2 In the Raman scattering spectrum of F, the D peak represents the amorphous carbon in the material, and the G peak represents the crystalline carbon. The G peak is significantly higher than the D peak, and the peak shape of the G peak is sharper, which indicates that the synthesized carbon quantum dots have a higher degree of crystallinity.

[0052] 2. Optical properties of NCl-CQDs

[0053] The optical properties of the synthesized NCl-CQDs were analyzed using UV-visible absorption and fluorescence spectroscopy. Figure 3 As shown, the UV-visible absorption spectrum has a maximum characteristic absorption wavelength at 336nm within the absorption band of 220 to 650nm, which may be attributed to the π-π* or n-π* transition of carbon nanomaterials. Further fluorescence property studies have shown that the optimal excitation wavelength (Ex) and the maximum emission wavelength (Em) are located at 390nm and 467nm, respectively. It is worth noting that the excitation spectrum and the emission spectrum show mirror symmetry, which is determined by the symmetry of the internal energy level structure of atoms or molecules, which is consistent with fluorescent carbon nanomaterials. The NCl-CQDs solution is brown under visible light and exhibits blue fluorescence under 365nm ultraviolet light ( Figure 3a illustration). This fluorescence emission behavior is due to the photoinduced charge separation and surface trapping, which leads to the radiative recombination between hole and electron pairs. In addition, the excitation wavelength dependence of the prepared NCl-CQDs was also studied. Figure 3 As shown in Figure B, the fluorescence spectra of NCl-CQDs at different excitation wavelengths (350-450nm) show typical excitation-dependent behavior. As the excitation wavelength increases, the emission wavelength red-shifts, showing a slight excitation wavelength dependence. The fluorescence emission intensity gradually increases as the excitation wavelength increases from 350nm to 390nm, and then gradually decreases as the excitation wavelength increases from 390nm to 450nm. This phenomenon is believed to be caused by the uneven size of the clusters. In order to further study its optical properties, the total luminescence spectrum (220-800nm) was obtained. The excitation-emission matrix spectrum shows that the excitation wavelength between 350 and 400nm exhibits certain excitation wavelength-independent characteristics, such as Figure 2 As shown in C. Figure 3 The CIE spectrum simulation software is also used to simulate the color coordinates (0.1395, 0.1839) in D, which can clearly see the location of the blue light of NCl-CQDs. In addition, according to the quantum yield calculation formula, the fluorescence quantum yield of the prepared NCl-CQDs is calculated to be 48.5%, which is a favorable choice for constructing a fluorescent sensing system with potential application prospects.

[0054] 3. XPS and FT-IR characterization of NCl-CQDs

[0055] X-ray photoelectron spectroscopy (XPS) was further used to study the chemical element composition and chemical state of NCl-CQDs. Figure 4 As shown in A, four distinct peaks of different elements can be seen: O1s, N1s, C1s, and Cl2p. Subsequently, the four elements were further characterized by high-resolution XPS spectroscopy. Figure 4 The high-resolution XPS of B showed four significant correlation peaks of C1s, which were 284.4 eV (CC / C=C), 285.5 eV (CN), 286.2 eV (CO) and 287.9 ​​eV (C=O). Figure 4C shows two different states of O1s: 531.4eV (C=O) and 532.6eV (CO). In addition, high-resolution XPS spectroscopy of N1s yielded three different peaks of the N element, including amino nitrogen (398.8eV), pyrrolic nitrogen (400.1eV), and pyridinic nitrogen (401.2eV). Finally, Cl2p also split into two different states of peaks: the peak corresponding to Cl2p (3 / 2) is 198.2eV, and the peak corresponding to Cl2p (1 / 2) is 199.8eV. XPS characterization can better prove that NCl-CQDs are composed of four elements: O, N, C, and Cl, which has important research significance for identifying the surface chemical properties and composition analysis of samples.

[0056] In the study of NCl-CQDs, FT-IR spectroscopy provides valuable information about the presence of different functional groups. In order to better understand the types of functional groups in NCl-CQDs, infrared spectroscopy scanning was performed. Figure 4 As shown in F, 3454cm-1 is N / OH stretching vibration, the weak peak at 2079cm-1 may be C≡C, which may be due to the weakened absorption of alkynes inside the carbon structure, 1638cm-1 is the stretching vibration peak of C=O / N, 1328cm-1 is CN stretching vibration, and 574cm-1 is C-Cl stretching vibration. The infrared spectrum shows that N and Cl are successfully doped in carbon quantum dots.

[0057] 4. Stability study of NCl-CQDs

[0058] In order to explore the stability of the carbon dots, stability tests were conducted under xenon lamp irradiation time, days of exposure, and different concentrations of NaCl salt solutions. The results showed that under xenon lamp irradiation for different time periods (0-70min), the fluorescence intensity of the carbon dots did not change significantly with the extension of irradiation time. Figure 5 As shown in A, the carbon dots were placed in a refrigerator at 4°C for about 8 days, and the fluorescence intensity was measured every day. Figure 5 B shows that the fluorescence intensity has not changed significantly. In addition, the salt tolerance of carbon dots was tested in NaCl salt solutions of different concentrations (0-1.0 M), and it can be seen that the fluorescence intensity remained almost unchanged. Figure 5 C. Therefore, from the above results, it can be shown that the prepared NCl-CQDs have good stability and can be better applied in actual life detection.

[0059] Example 3

[0060] 1. Construction of “ON-OFF-ON” sensing system

[0061] The maximum fluorescence emission wavelength of the synthesized NCl-CQDs fluorescent probe under 390nm excitation is 467nm. At this time, the fluorescence signal of NCl-CQDs is in the on state. However, when sodium 2,6-dichloroindophenolate is added to the sensing system, the fluorescence intensity of NCl-CQDs is significantly quenched, resulting in the fluorescence signal being in the off state. Subsequently, ascorbic acid (AA) is added to the NCl-CQDs / sodium 2,6-dichloroindophenolate solution to restore the fluorescence signal to the "ON" state, as shown in Figure 2. Figure 6 Therefore, the “on-off-on” fluorescence sensing system based on NCl-CQDs / 2,6-dichloroindophenol sodium-AA was successfully constructed.

[0062] 2. Research on optimization of sensing system conditions

[0063] In order to study whether the fluorescence intensity is affected by its reaction time, it is necessary to study the reaction time between the fluorophore and the specific analyte. For the NCl-CQDs / DCIP sensing system, the fluorescence emission intensity was measured at an excitation wavelength of 390 nm and measured every 60 seconds. Figure 7 As can be seen in A, as the reaction time increases, the fluorescence intensity gradually decreases, and after 5 minutes, the fluorescence intensity tends to be stable, indicating that the optimal reaction time of the system is 5 minutes. At the same time, the reaction time of NCl-CQDs / DCIP and AA was studied, and it was measured every 30 seconds. It was found that after 1.5 minutes, the fluorescence intensity no longer increased but began to decline, and the fluorescence intensity reached the highest at 1.5 minutes, as shown in Figure 1. Figure 7 As shown in B.

[0064] Example 3 Experimental Optimization Design

[0065] 1. Optimization of DCIP concentration

[0066] like Figure 8 As shown in the figure, fluorescence measurement was carried out. Sodium 2,6-dichloroindophenol was added from low concentration to high concentration (0μM, 2.26μM, 4.6μM, 13.8μM, 15.6μM, 20.7μM, 23.6μM, 24.8μM, 26.3μM, 27.7μM, 29.4μM, 30.77μM) into the optimized NCl-CQDs solution. As the concentration of sodium 2,6-dichloroindophenol increased, the fluorescence intensity of NCl-CQDs decreased, and there was a good rising and falling relationship between NCl-CQDs and sodium 2,6-dichloroindophenol.

[0067] 2. Selectivity of NCl-CQDs sensing system

[0068] In order to verify whether the fluorescent sensor can be well applied to actual sample detection, its selectivity was investigated. 10 μL of AA and Ba were added to the NCl-CQDs / 2,6-dichloroindophenol sodium system. 2+ , Ca 2+ 、Co 2+ , Cu 2+ , Fe 2+ , Fe 3+ , Hg 2+ , K + 、Ni 2+ , Sr 2+ , L-alanine, L-cysteine, L-threonine, L-arginine, L-histidine, L-methionine, L-leucine, L-serine, L-aspartic acid, L-valine, L-isoleucine, and obtained an intriguing result. Fig. 9 It can be seen that when the concentration of interfering substances is 100 times that of AA, only ascorbic acid (AA) can increase the fluorescence emission intensity of NCl-CQDs / DCIP again, while other substances have little effect on the fluorescence intensity. The above results show that the NCl-CQDs / DCIP system has good selectivity for AA and can be further applied to the detection of actual samples.

[0069] 3. Construction of linear relationship between NCl-CQDs-DCIP and AA system

[0070] Add 1×10 -5 mol / L~1×10 -4 AA in the mol / L range, when the excitation light is set to 390nm and the slit width is 3×5, the fluorescence intensity of the NCl-CQDs-2,6-dichloroindophenol sodium-AA system is measured in the range of 400-600nm. The concentrations of AA are 9.09μM, 23.07μM, 33.3μM, 44.4μM, 52.38μM, 58.33μM, 65.51μM, 70.58μM, 74.35μM, 77.27μM, 79.59μM, 81.48μM, 83.05μM, 84.37μM, 85.5μM from bottom to top. As the concentration of AA increases, AA restores the fluorescence emission peak. When the concentration of AA is 85.5μM, the fluorescence intensity returns to the highest, as shown in Figure 2. Fig.10 As shown in A.

[0071] The working curve is drawn with the fluorescence intensity of NCl-CQDs-2,6-dichloroindophenol sodium-AA as the ordinate and the concentration of AA as the abscissa. Fig.10B. The results show that when the concentration is between 9.09μM and 65.51μM, the linear equation is Y=4.606X+102.438, R 2 =0.991, the linear range is 144.31μM~404.18μM, and the detection limit is 13.137μM. Fig.10 C; when the concentration is between 70.58μM and 85.5μM, the linear equation is Y=19.429X-917.395, R 2 =0.990, the linear range is 453.90μM~743.78μM, and the detection limit is 0.80μM. Fig.10 As shown in D, it can be explained that there is a good linear relationship between AA and NCl-CQDs-2,6-dichloroindophenol sodium system, which can realize the detection of AA in actual samples.

[0072] Example 4 Practical application of "ON-OFF-ON" sensing system

[0073] Therefore, it is necessary to evaluate the feasibility of fluorescent sensors to detect analytes in actual samples to evaluate the proposed NCl-CQDs / DCIP-AA sensing platform for the detection of actual samples in serum, and the average recovery of AA obtained was 97.20% to 103.90%, and its minimum relative standard deviation did not exceed 0.65%, which was within the acceptable range, as shown in Table 1. In summary, the NCl-CQDS / DCIP-AA fluorescence sensing platform can better monitor the content of AA in serum and has certain practical application potential.

[0074] Table 1 Detection of AA in actual samples

[0075]

[0076]

[0077] Discussion on the mechanism of “ON-OFF-ON” sensing system

[0078] like Fig.11 As shown in A, NCl-CQDs exhibited obvious fluorescence absorption, but after adding DCIP, the fluorescence was quenched. In order to prove the quenching mechanism of its fluorescence intensity, we studied its UV-visible absorption spectrum (UV-vis). Fig.11B shows that NCl-CQDs has an obvious ultraviolet absorption peak at around 287nm, and DCIP has a sharp absorption peak at 270nm. When DCIP is introduced into NCl-CQDs, its absorption peak shows red shift and absorption peak enhancement. It is preliminarily inferred that there are potential n→π* and π→π* transitions between the two, which cause the electrons on the bonding orbitals in their molecules to absorb energy and be excited to the antibonding orbitals, thereby forming a non-luminescent ground state complex (NCl-CQDs / DCIP) through photoelectron induced transfer, resulting in fluorescence quenching.

[0079] Subsequently, in order to prove that the fluorescence intensity of the NCl-CQDs / DCIP system gradually recovered after the introduction of AA, the UV-vis mechanism was also explored. Fig.11 As shown in Figure C, AA has no UV absorption peak. When AA is introduced into the NCl-CQDs / DCIP system, the UV absorption peak disappears and a significant red shift occurs. This is because the redox electron transfer between DCIP and AA causes a chemical reaction in the base state. At this time, the reduced ascorbic acid reduces 2,6-dichloroindophenol sodium and is oxidized to dehydrogenated ascorbic acid, thereby restoring the fluorescence of NCl-CQDs. Therefore, using photoelectron induced transfer and redox reaction, we successfully constructed an NCl-CQDs / DCIP / AA "ON-OFF-ON" fluorescence sensing system, realizing rapid and efficient detection of AA.

[0080] In summary, the present invention synthesizes NCl-CQDs by dehydration carbonization method. The synthesized NCl-CQDs particles are evenly distributed and have good dispersibility. The average particle size is 2.96nm, and it has obvious luminescence characteristics and excitation wavelength dependence. A relatively novel "switch-on" method for detecting AA is established based on the NCl-CQDs fluorescent probe. In the experiment, NCl-CQDs was used as a fluorescent probe, and based on the principle that the fluorescence spectrum of NCl-CQDs changes due to the photoinduced electron transfer between 2,6-dichloroindophenol sodium and NCl-CQDs, an "on-off" type fluorescence sensor of NCl-CQDs and 2,6-dichloroindophenol sodium was constructed. Then, the specific reaction between 2,6-dichloroindophenol sodium and AA was used to continue to introduce AA into the system to construct an "off-on" type fluorescence sensor. Based on the specific reaction between AA and sodium 2,6-dichloroindophenol, AA competes with sodium 2,6-dichloroindophenol on the surface of NCl-CQDs, thereby restoring the UV-visible absorption spectrum and fluorescence signal of NCl-CQDs, and then establishing an "on-off-on" type fluorescence sensor of NCl-CQDs / sodium 2,6-dichloroindophenol+AA. The established fluorescence analysis method can be used for the detection of AA in actual sample serum through spike recovery, indicating that the fluorescence sensing system has better utilization value for AA in actual complex samples. Compared with traditional detection methods, this method has good application prospects for monitoring human health levels.

[0081] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an "on-off-on" fluorescent nanosensor based on NCl-CQDs, characterized in that: Using nitrogen-chlorine co-doped carbon quantum dots NCl-CQDs as fluorescent needles, 2,6-dichloroindophenol sodium DCIP as a fluorescence quencher, and ascorbic acid AA as a fluorescence recovery agent, the three specifically combine in a specific sample addition order to obtain an "on-off-on" fluorescent nanosensor; the specific steps are as follows: Step 1: Using glucose Glu, ethylenediamine EDA and concentrated hydrochloric acid HCl as raw materials, NCl-CQDs with a nitrogen-chlorine co-doped carbon quantum dot concentration of 44.4 μM were prepared by dehydration exothermic carbonization method; when the excitation wavelength was 390 nm, the maximum fluorescence emission wavelength of NCl-CQDs was 467 nm, and the fluorescence intensity was in the "ON" state; Step 2: When 1 mL of 30.77 μM DCIP was introduced into 1 mL of 44.4 μM NCl-CQDs solution, at an excitation wavelength of 390 nm, the fluorescence of NCl-CQDs was quenched due to the photoinduced electron transfer effect, and the fluorescence emission intensity dropped from 910 nm to about 50 nm, at which time the fluorescence was in the "OFF" state; Step 3. Continuously introducing 85.5 μM AA into the NCl-CQDs / DCIP system can significantly restore the fluorescence intensity of NCl-CQDs. When the excitation wavelength is 390 nm, the signal intensity can increase from 148 nm to about 748 nm, at which time the fluorescence intensity is in an "ON" state; thus, an "on-off-on" fluorescence nanosensor of NCl-CQDs / 2,6-dichloroindophenol sodium + AA is obtained.

2. The method for preparing an "on-off-on" fluorescent nanosensor based on NCl-CQDs according to claim 1, characterized in that: The preparation steps of the nitrogen-chlorine co-doped carbon quantum dots NCl-CQDs are as follows: Step (1) 0.8 g glucose and 12 ml EDA were completely dissolved in 20 mL ultrapure water by ultrasound and vortexing; Step (2) Add 4 ml of concentrated hydrochloric acid to the above mixed solution, releasing a large amount of white smoke and heat. After cooling to room temperature, a brown-yellow substance is obtained; Step (3) The brown-yellow substance was dissolved in 50 ml of ultrapure water, and the solution was then centrifuged at 4000 rpm for 10 min, and then microfiltered using a 0.22 μM filter to obtain a brown solution, and the solution was freeze-dried to obtain pure NCl-CQDs brown solid powder.

3. The method for preparing an "on-off-on" fluorescent nanosensor based on NCl-CQDs according to claim 1, characterized in that: In step 1, the fluorescence quantum yield of the prepared NCl-CQDs was 48.5%.

4. The method for preparing an "on-off-on" fluorescent nanosensor based on NCl-CQDs according to claim 1, characterized in that: In step 2, the reaction time is 5 min.

5. The method for preparing an "on-off-on" fluorescent nanosensor based on NCl-CQDs according to claim 1, characterized in that: In step 3, the reaction time is 1.5 min.

Citation Information

Patent Citations

  • Carbon quantum dot / aurum cluster ratiometric fluorescent probe for detection of cadmium ion and ascorbic acid

    CN106047342A

  • Fluorescence sensor and preparation method and application thereof

    CN110702655A

  • Detection method for determining isoniazide based on dual-emission carbon quantum dot ratio fluorescent probe

    CN116678859A